Development, characterization, and modeling of the dynamic mechanical properties of a highly flexible novel SWCNT/EMA nanocomposite. (March 2023) - Sit, Subhashis; Chakraborty, Goutam; Das, Narayan Chandra
Abstract: This study investigates the effect of single-walled carbon nanotube (SWCNT) reinforcement on the mechanical and dynamic mechanical properties of ethylene methyl acrylate (EMA) polymer. A novel SWCNT/EMA nanocomposite is fabricated by a facile, cost-effective, and industry-viable solution mixing technique varying the SWCNT content from 1 to 10 wt%. The crystal structure and the purity of the SWCNTs are investigated by Raman spectroscopy and X-ray diffraction (XRD) analysis. In contrast, the thermal properties of EMA polymer are studied using differential scanning calorimetry (DSC). Material morphology of the fabricated nanocomposite has been elucidated through a scanning electron microscope (SEM) and transmission electron microscope (TEM) to validate the distribution, dispersion, and interaction of the SWCNTs. The tensile properties exhibit the improvements in strength and stiffness of the nanocomposites with SWCNT reinforcements, and the highest increment in UTS and E is observed as 45% and ten times, respectively, for 10 wt% SWCNT loaded composite as compared to pure EMA. The dynamic mechanical properties in terms of storage modulus, loss modulus, and damping factor were characterized using a dynamic mechanical analyzer (DMA) and shows their unique dependence on combined variations of frequency of loading, temperature, and concentration of reinforcement loadings. The reinforcing effects of SWCNTs are justified by the increase in storage modulus and glass transition temperature by 140% and 4.5 °C. A modified Maxwell model of viscoelasticity has been used in the reduced variables method to model and understand the dynamic properties in a concise manner (Reduced dynamic rigidity and viscosity as a combined function of temperature, frequency, and reinforcement loading) for its potential application in industry and academia to understand the material's capability for the dissipation of vibrational energies, especially in aerospace and automobile applications. Graphical Abstract: ga1 Highlights: Fabrication of a novel nanocomposite using solution mixing technique. Characterization of dynamic mechanical with temperature and SWCNT loading. Dynamic properties characterization with external loading frequency variation. Reduced variables method to obtain two universal dispersion functions. Developed a modified Maxwell Model to predict the reduced dynamic properties.